Monitoring health-related quality of life in paediatric practice: development of an innovative web-based application - Heymans Hugo SA; van Rossum Marion AJ; Engelen Vivian; Haverman Lotte; Grootenhuis Martha A (BMC, 2011)
Abstract Background Health Related Quality of Life (HRQOL) questionnaires are increasingly used in clinical practice. These Patient Reported Outcomes (PROs) are provided to the paediatrician to facilitate communication with patients during a consultation. The aim of the current article is to describe the development and introduction of a new web-based application for the use of PROs in daily paediatric clinical practice. Methods Currently, the use of PROs in daily clinical practice is very time consuming and often has logistical problems. The use of a web-based programme can overcome these problems and contributes to an improved use of PROs in clinical practice. We therefore developed an easily accessible website (KLIK) for outpatient treatment and a training programme for paediatricians to maximize the effectiveness and the practical use of PROs (KLIK PROfile). Results The KLIK study was launched in August 2008 to evaluate the use of the KLIK PROfile in daily clinical practice. The KLIK study evaluates whether feedback from HRQOL data could influence patient satisfaction with the consultation, the advice given, the type of referrals and topics discussed. In this multicentre study, a control group (without the use of the KLIK PROfile) is compared to an intervention group (with the use of the KLIK PROfile). A sequential cohort design is chosen to avoid contamination between the study groups. Conclusions Based on the positive experiences with the use of the KLIK PROfile acquired during the study we conclude that the KLIK PROfile may contribute to systematically monitor and discuss HRQOL issues during consultations. The next steps will be a comprehensive evaluation of the KLIK study data and the implementation of the KLIK PROfile in daily clinical practice in different patient groups.